Results of the Treatment of Chronic, Refractory CRPS with Ketamine Infusions: a Preliminary Report - Puchalski, P.; Zyluk, A. (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2016)
Chronic, refractory complex regional pain syndrome remains very difficult to treat. A sub-anaesthetic low-dose ketamine has shown promise in advanced CRPS. We investigated the efficacy of ketamine in anaesthetic dosage in chronic, refractory CRPS patients that had failed available standard therapies. 5 female patients, aged a mean of 34 years with long-standing, a mean of 8 years’, CRPS received ketamine in anaesthetic dosage over 10 days. The patients received 1–5 ketamine courses. The effect of gradual pain reduction was observed beginning on the 4th–5th day of treatment, associated with a decrease in the intensity of the allodynia (pain at light touch). No improvement in function (finger range of motion, grip strength) of the affected hands was noted in any patient. This beneficial analgesic effect was confined to 1.5–2.5 months after treatment and then pain relapsed to the baseline level. The results of this study show a short-term analgesic effect for this therapy, with no effect on movement and function of the affected limbs. Nevertheless, this method brings hope to the most severely ill patients who cannot be offered any other reasonable treatment option.
Keywords: chronic regional pain syndrome; ketamine infusion